Grãos destilados de milho como aditivo na ensilagem do capim-elefante - Matter, Edegar (2020)
The silage of tropical grass is a good alternative to circumvent the low supply of pasture during seasons. From climatic seasonality. Of the tropical grass species, elephant has potential for ensiling due to it high biomass production. However, when this forage has good nutritional value, the dry matter (DM) content is reduced, which causes undesirable fermentations, decreasing the nutritional quality of the silage. To minimize these losses, researchers have been carried out studies of elephant grass forage with moisture absorbing products with high DM content. In this work, two experiments were carried out with elephant grass cultivar Canará, by adding Dried Distillers Grains (DDG) and Wet Distillers Grains (WDG), co-products of corn used for ethanol production. The aim of this work was to verify the fermentation pattern and to evaluate the nutritional and digestive value of Canará grass silage, added with increasing levels of DDG and WDG. Both experiments were conducted at the Experimental Farm of the Federal University of Mato Grosso in the Santo Antônio do Leverger. The design used in the experiments was completely randomized, with 6 treatments (0; 5; 10; 15; 20 and 30 % of aditives inclusion) and 4 replications. The variables measured for the experiments were: buffer capacity ( BC), stable carbohydrates (SC), fermentative coefficient (FC), calosses by gases (GL) and effluents (EFLU); contents of dry matter recovery (DMR); hydrogen potential (pH); ammoniacal nitrogen (N-NH3); dry matter (DM); mineral matter (MM); acid detergent fiber (ADF); neutral detergent fiber (NDF); neutral detergent fiber free of ash and protein (NDFap); crude protein (CP); neutral detergent insoluble protein (NDIP); acid detergent insoluble protein (ADIP); total digestible nutrients (TDN) and liquid lactating energy (LLE). The data were subjected to regression analysis at the level of 5 % and 1 % probability, using the statistical program SISVAR®. For DDG, as the inclusion levels increased, there was a quadratic effect for: GL, N-NH3, MM, NDF, NDFap, NDIP and TDN; and linear effect for: BC, FC, EFLU, DMR, pH, DM, CP, ADIP, LLE and ADF. In the experiment with WDG, as the inclusion levels increased, there was a quadratic effect for: N-NH3, NDIP and ADIP; increasing linear effect for: SC, FC, pH, DM, CP, NDIP (% DM), TDN and LLE; decreasing effect for: BC, EFLU, MM, ADF, NDF and NDFcp; and there was no significant effect for GL and DMR. Both additives provided silage with a good fermentation pattern, losses were minimized, and an increase in the nutritional value of Canará elephant grass silage was provided. Both additives are recommended doses of 20% of inclusion, with no restrictions on the use of higher doses for the additive WDG, however for DDG you should check if the additive will not cause a sharp increase in the dry matter of the material to be ensiled.